The efficacy of cumulative cisplatin dose on survival in patients with locally advanced cervical cancer treated with definitive chemoradiotherapy: A multicenter study by the Turkish Oncology Group (TOG) - Akyildiz, Arif; Gultekin, Melis; Yigit, Ecem; Demir, Ecem; Ismayilov, Rashad; Ahmed, Melin Aydan; Arik, Zafer (Lippincott Williams & Wilkins, 2024)
[Abstract Not Available]
Special Clinical Science Symposia -- MAY 29-29, 2024 -- ELECTR NETWORK